2018
DOI: 10.1016/j.chembiol.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing HAMI3379 to Block GPR17 and Promote Rodent and Human Oligodendrocyte Differentiation

Abstract: Identification of additional uses for existing drugs is a hot topic in drug discovery and a viable alternative to de novo drug development. HAMI3379 is known as an antagonist of the cysteinyl-leukotriene CysLT receptor, and was initially developed to treat cardiovascular and inflammatory disorders. In our study we identified HAMI3379 as an antagonist of the orphan G protein-coupled receptor GPR17. HAMI3379 inhibits signaling of recombinant human, rat, and mouse GPR17 across various cellular backgrounds, and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…While our analysis revealed the essential roles of GPR17 on the dorsal-ventral pattern formation of the spinal cord in chick, the effect in the mouse neural tube has been unknown, and at least, does not seem to be critical [27,45,46], as GPR17 -deficient mice are viable. This is probably due to the redundant roles of the multiple GPCRs expressed in the neural tube.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While our analysis revealed the essential roles of GPR17 on the dorsal-ventral pattern formation of the spinal cord in chick, the effect in the mouse neural tube has been unknown, and at least, does not seem to be critical [27,45,46], as GPR17 -deficient mice are viable. This is probably due to the redundant roles of the multiple GPCRs expressed in the neural tube.…”
Section: Discussionmentioning
confidence: 95%
“…GPR17 expression is gradually upregulated during the demyelination induced by the glial toxin Lysolecithin [45]. Conversely, the antagonist supporting GPR17 increases the oligodendrocyte cell number [46]. Moreover, the proliferation of the Olig2-expressing cells is encouraged in the situation where GPR17 is attenuated [45].…”
Section: Discussionmentioning
confidence: 99%
“…Under this condition, we reasoned that the pharmacological manipulation of GPR17 could be useful in re-establishing a correct receptor activity and in restoring OPC functions. In this contest, the use of either an agonist or an antagonist is still a debated issue likely because the conflicting results of in vitro experiments [28,[56][57][58][59][60][61][62][63][64]. Previous works had already demonstrated that the in vivo pharmacological inhibition of GPR17 is able to improve WM integrity, increasing the number of mature oligodendrocytes and promoting remyelination [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot exclude that the beneficial in vivo effect of the GPR17 agonist presented here could be a consequence of receptor adaptive changes due to long term agonist administration in vivo. This could explain why, in some in vitro studies, GPR17 inactivation at specific oligodendrocyte maturation stages could also improve oligodendrocyte differentiation [21]. In a similar way, in the middle cerebral artery occlusion model, acute treatment with the non-selective antagonist cangrelor resulted in a reduction of the brain infarct size [13].…”
Section: Plos Onementioning
confidence: 94%
“…Accordingly, GPR17 overexpression in late OPCs in vitro [16] and in transgenic mice results in loss of oligodendrocytes as well as myelination arrest [15]. Its localization on the extracellular membrane of myelinating cells and its behavior in pathophysiological conditions make GPR17 an attractive 'druggable' target [11,[20][21][22][23]. Small molecules highly-selective for this receptor could be developed and used either alone or in synergy with other drugs able to control immune response and inflammation.…”
Section: Introductionmentioning
confidence: 99%